17β-Estradiol Protects Lymphocytes against Dopamine and Iron-induced Apoptosis by a Genomic-independent Mechanism : Implication in Parkinson's Disease (2001)
ABSTRACT: Dopamine (DA) in combination with iron (Fe2+) has been demonstrated to induce apoptosis in neuronal-like PC12 cells by an oxidative stress mechanism. To get a better insight of cell death and protective mechanisms in DA/Fe2+-induced toxicity, we investigated the effects of DA/Fe2+ and the antioxidant action of 17β-estradiol (E2) in peripheral blood lymphocytes (PBL). We found that DA/Fe2+-induces apoptosis in PBL via a hydrogen peroxide (H2O2)-mediated oxidative mechanism, which in turn triggers a cascade of molecular events requiring RNA and de novo protein synthesis. We have also demonstrated that E2 prevents significantly DA/Fe2+-induced apoptosis in PBL by directly inhibiting the intracellular accumulation of peroxides generated by DA/Fe2+-reaction. This protective activity is independent of the presence or activation of the estrogen receptors (ERs). These data further support and validate our previous hypothesis that DA/Fe2+/H2O2 could be a general mediator of oxidative stress through a common cell death mechanism in both neuronal and nonneuronal cells. These findings may be particularly relevant to the potential approaches to rescue and prolong the survival of neurons by estrogens in patients with Parkinson's disease (PD).